Investigating the concentration of radionuclides in wells used as drinking water in northern Nigeria. A case study of Jos metropolis - Godwin, I. (KamGU by Vitus Bering, 2021)
The increasing health effects of nuclear radiation occasioned by the enhanced human activities in the environment necessitated the need for constant investigation and assessment of radiological impact on the general populace within a confined area. Based on this, Twenty two (22) (Hand dug and motorized) well water samples were collected from various locations distributed across Jos Metropolis, Jos North LGA, Plateau State, Nigeria and analyzed for the concentration activity of these radionuclides (40K, 210Pb, 224Ra, 232Th, 238U) using radiochemical analysis technique, a high resolution gamma ray Spectrometry and a radon emanometry technique. The estimated mean concentration activity of 40K, 210Pb, 224Ra, 232Th and 238U in well water samples use as drinking water were determined. The mean concentration ranges from 1.36±0.51 Bq/l to 5.75±1.30 Bq/l. The mean concentration of 40K in well water samples ranges from 3.80±1.19 Bq/l to 2.05±0.30 Bq/l. The mean concentration of dissolved 224Ra in well water samples collected varies from 5.75±1.30 Bq/l to 1.95±0.58 Bq/l. 210Pb has an average concentration of 2.68 ± 0.80 Bq/l to 1.97±0.87 Bq/l. 232Th and 238U had average concentrations of 3.09 ± 0.57 Bq/l to 1.89±0.24 Bq/l and 5.41 ± 1.37 Bq/l to 1.36±0.51 Bq/l respectively. 210Pb and 224Ra were slightly above the recommended limits of 0.10 Bq/l and 1.00 Bq/l respectively, this can be attributed to the geological formation of the sampled area. 232Th and 238U where within the accepted standard limits of 1.00 Bq/l and 10.00 Bq/l recommended value by WHO (World Health Organization) and ICRP (International commission on radiological protection). Activity concentrations of measured radionuclides are in general decreasing in this order: 238U > 40K > 224Ra > 232Th > 210Pb for well water samples within Jos North LGA, respectively.